Serenade by "Tenors," conductors on Amtrak
Three Amtrak conductors are pictured standing in the train isle singing together. All men are wearing a white dress shirt with different patterned ties. The conductor on the left (wearing silver glasses) is wearing a black apron with a name tag and a button with the American Flag inside a United States map. The conductor in the middle has a walkie talkie on their collar, and has a pocket protector with various pens and markers in their shirt pocket. The conductor on the right also has a pocket protector with various pens and markers in their shirt pocket, and wearing a hat that says 'Amtrak Conductor'.